Pulmonary Arterial Lesions in New World Camelids in Association With Dicrocoelium dendriticum and Fasciola hepatica Infection. (November 2015) - Hilbe, M.; Robert, N.; Pospischil, A.; Gerspach, C.
In Switzerland, dicrocoeliasis is regarded as the most significant parasitic infection of llamas and alpacas. Fasciola hepatica infestation is also a problem but less common. The aim of the present retrospective study was to evaluate the lungs of New World camelids (NWCs) for evidence of arterial hypertension in association with liver changes due to liver fluke infestation. The lungs of 20 llamas and 20 alpacas with liver fluke infestation were histologically evaluated. The hematoxylin and eosin and van Gieson (VG)–elastica stains as well as immunohistology for the expression of α–smooth muscle actin (α-SMA) were used to visualize the structures of arterial walls. Parasitology of fecal matter (11 llamas and 17 alpacas) confirmed that most of these animals were infested with both Dicrocoelium dendriticum and other gastrointestinal parasites. In most cases (10/12 llamas, 4/6 alpacas), liver enzyme activity in serum was elevated. Histologically, arteries in the lungs of 9 of 20 llamas (45%) and 3 of 20 alpacas (15%) showed severe intimal and adventitial and slight to moderate medial thickening, which was confirmed with α-SMA and VG-elastica staining. All animals exhibited typical liver changes, such as fibrosis and biliary hyperplasia, in association with the presence of liver flukes. This study shows that liver flukes can induce proliferative changes in lung arteries in NWCs that resemble those seen with pulmonary arterial hypertension due to liver parasites in humans. However, the degree of liver fluke infestation was not correlated with the extent of liver damage, or with the amount of thoracic or abdominal effusion or pulmonary arterial changes.